2014
DOI: 10.1186/1478-4491-12-32
|View full text |Cite
|
Sign up to set email alerts
|

The implications of the feminization of the primary care physician workforce on service supply: a systematic review

Abstract: There is a widespread perception that the increasing proportion of female physicians in most developed countries is contributing to a primary care service shortage because females work less and provide less patient care compared with their male counterparts. There has, however, been no comprehensive investigation of the effects of primary care physician (PCP) workforce feminization on service supply. We undertook a systematic review to examine the current evidence that quantifies the effect of feminization on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 24 publications
6
120
0
14
Order By: Relevance
“…While several attempts, including our own study, have aimed at improving understanding of health workforce issues and implications of aging and timing of physicians’ work, future policy research should continue forecasting physician retirement trajectories and human resource strategies in ways that can account for older physicians who want to remain in clinical practice beyond traditional retirement age [17, 72, 73]. Recommendations for next steps in policy reform at the organizational and health system level may come from within hospital and other related organizations which aim to address intentions to leave by improving psychosocial working conditions for the medical profession [64] and scaling back workloads to retain the best talent in experienced physicians [42].…”
Section: Discussionmentioning
confidence: 99%
“…While several attempts, including our own study, have aimed at improving understanding of health workforce issues and implications of aging and timing of physicians’ work, future policy research should continue forecasting physician retirement trajectories and human resource strategies in ways that can account for older physicians who want to remain in clinical practice beyond traditional retirement age [17, 72, 73]. Recommendations for next steps in policy reform at the organizational and health system level may come from within hospital and other related organizations which aim to address intentions to leave by improving psychosocial working conditions for the medical profession [64] and scaling back workloads to retain the best talent in experienced physicians [42].…”
Section: Discussionmentioning
confidence: 99%
“…A related but slightly different perspective on this theme comes from a study in Scotland, which found that women primary care providers tend to work fewer hours and are less likely to engage in teaching and administrative duties than their male colleagues, suggesting important implications for countries’ physician workforces [25]. However, a systematic review of studies across multiple high income countries found that these differences in hours were due primarily to women’s role in childrearing [2]. …”
Section: Introductionmentioning
confidence: 99%
“…The feminisation has modified the traditional model of professional organisation because women have developed strategies to adapt their working time to the requirements of their private life. 12 However, even if they still work fewer hours than men, 11 the difference between women and man concerning the working time tends to decrease. 12 Whatever the sex, young GPs regulate their working time to maintain a good quality of life and balance work and private life.…”
Section: Discussionmentioning
confidence: 99%